The impact of using surgical masks and non-masks when exercising on heart rate, calories and VO2max during the Covid-19 pandemic - Nugraha, Afif Dwi; Yudanto, Yudanto; Bahri, Samsul (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The use of surgical masks during exercise is still a matter of controversy. Thus the aim of this study was to see the effect of using surgical masks and non masks on heart rate, VO2max and calories during exercise. This study used a quasi-experimental method with a posttest-only crossover design approach. The instrument used in this study was the VO2max test using the Cooper Test (running as far as 2.4 km). The total subjects were 12 healthy men with a mean age of 19.87 ± 1.24 years; height, 166.81 ± 6.31 cm; and weight, 56.30 ± 3.79 kg; BMI, 20.06 ± 0.95 kg / m-2. The results showed that the use of masks during aerobic endurance exercise had no effect on heart rate and VO2max, a significant difference occurred in energy expenditure which included the number of calories while using surgical masks (p = 0.001). Aerobic exercise using a surgical mask and without the use of a mask is safe and possible. Despite the fact that wearing a mask when exercising is a little uncomfortable, the use of a surgical mask has only a small effect on physiological parameters during exercise